The impaired response of nasal epithelial cells to microplastic stimulation in asthma and COPD - Magdalena Paplińska-Goryca; Paulina Misiukiewicz-Stępień; Monika Wróbel; Katarzyna Mycroft-Rzeszotarska; Dorota Adamska; Julia Rachowka; Milena Królikowska; Krzysztof Goryca; Rafał Krenke (Scientific Reports)
Abstract Microplastic particles from the air are inhaled and accumulate in the lungs, potentially causing immunological reactions and airway tissue injury. This study aimed to evaluate the biological effects of polyamide fibres on nasal epithelium co-cultivated with macrophages in control, asthma, and COPD groups. Nasal epithelial cells alone or in co-culture with monocyte-derived macrophages were exposed to polyamide fibres for 48 h. We identified 8 differentially expressed genes (DEGs) in controls, 309 DEGs in asthma (including ANKRD36C, BCL2L15, FCGBP, and IL-19), and 22 DEGs in COPD (e.g., BCL2L15, IL-19, CAPN14, PGBD5, PTPRH), particularly in epithelial/moMφ co-cultures. Microplastic exposure induced inflammatory cytokine secretion only for IL-8 production in controls (epithelial/ moMφs co-culture) and asthmatic (monoculture) epithelial cells in contrast to PM2.5, which was a strong inflammatory inducer. Gene Ontology analysis revealed that microplastic exposure affected sterol and cholesterol biosynthesis, secondary alcohol metabolism, and acetyl-CoA metabolism in asthma, and cell motility, chemokine signaling, leukocyte migration, and chemotaxis in COPD. Microplastic stimulation altered the response of airway epithelial cells in obstructive lung diseases differently than in controls, linking to Th2 inflammation, stress response modulation, and carcinogenesis. Asthmatic and COPD epithelial cells are more susceptible to damage from microplastic fibre exposure.